Value of Bangladeshi Commercial Banks: Influence of Investment Decision, Financing Decision, and Dividend Policy - Md. Muniruzzaman; Md. Kaysher Hamid; Shawon, Md. Lifatuzzaman (The Es Accounting And Finance, 2025)
The financial performance and valuation of Bangladeshi commercial banks are influenced by investment decisions, financing decisions, and dividend policy, yet their collective impact on firm value remains a critical concern. The banking sector faces challenges such as fluctuating profitability, rising non-performing loans, and inconsistent dividend policies, creating uncertainty in firm valuation. This study examines the relationship between these financial decisions and firm value by analyzing data from the annual reports of 28 banks listed on the Dhaka Stock Exchange (DSE) from 2017 to 2022. Investment Decisions, Financing Decisions, and Dividend Policy are represented by the Price Earnings Ratio, Debt Equity Ratio, and Dividend Payout Ratio, respectively, while firm value is measured using Price to Book Value (PBV), Tobin’s Q (TQ), and Share Price (SP). Using STATA software, the study conducts descriptive analysis, correlation analysis, and panel data regression. The findings reveal that Investment and Financing Decisions significantly affect firm value, whereas Dividend Policy shows no significant impact. The study provides practical insights for companies to optimize their financial strategies for long-term value creation. However, it is limited to selected banks and does not account for external macroeconomic factors.